2022
DOI: 10.1002/smll.202105185
|View full text |Cite
|
Sign up to set email alerts
|

Prussian‐Blue Analogue‐Derived Hollow Structured Co3S4/CuS2/NiS2 Nanocubes as an Advanced Battery‐Type Electrode Material for High‐Performance Hybrid Supercapacitors

Abstract: much attention because of their advantages of quick charge/discharge property, superior power density, and long-lasting and eco-friendly feature. [3,4] However, active materials which consist of inherent synergistic properties should be chosen to improve the capacity performance in the SCs. Typically, the active materials (Faradaic redox nature) are constructed with transition metal oxides/hydroxides and chalcogenides. [5] The fabricated electrodes with transition metal oxides/hydroxides show great redox prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 70 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…84,105 Sometimes, due to different precursors (sulfur, selenium, or NaH 2 PO 2 powder) and different growth mechanisms of the derivative crystals, the same structure evolves into different morphologies. 19,89 Heat-treatment parameters can also affect the design. It has been shown that treating PBA particles under the same atmosphere but with different temperatures can result in different oxide morphologies.…”
Section: Structure Design and Pbd Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…84,105 Sometimes, due to different precursors (sulfur, selenium, or NaH 2 PO 2 powder) and different growth mechanisms of the derivative crystals, the same structure evolves into different morphologies. 19,89 Heat-treatment parameters can also affect the design. It has been shown that treating PBA particles under the same atmosphere but with different temperatures can result in different oxide morphologies.…”
Section: Structure Design and Pbd Characteristicsmentioning
confidence: 99%
“…8–10 Calcination methods produce oxides, 11–13 while annealing generates carbides, 14,15 alloys, 16,17 or metal nanoparticles with different compositions. 18–22 Pre-treatments can regulate the morphology of the derivatives or introduce heteroatoms. 22–24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the capacity augments slowly during the first 1000 initial cycles, indicating initial activation and infiltration of the electrolyte into the electrode. [ 45 ] Meanwhile, the coulombic efficiency of Co 3 S 4 @NiCo‐LDH/NF maintains almost 100% in the period of 5000 cycles, proving the miraculous reversibility. Compared with the electrochemical capabilities of the TMSs‐ and LDH‐related research results reported recently (Table S2, Supporting Information), the Co 3 S 4 @NiCo‐LDH/NF electrode emerges a great advantage in achieving high capacity and excellent stability.…”
Section: Resultsmentioning
confidence: 99%
“…4,11 Recently, intricate structures such as hollow nanocubes and nanoframes (NFs) composed of transition metals (e.g., Ni, Fe, Co, Mn) have attracted great interest as promising materials for realizing new properties. 4,12,13 In our study, Ni-Fe PBA nanocubes (Ni-Fe NCs) are converted to Ni-Fe PBA nanoframes (Ni-Fe NFs) via a sonochemical etching process with hydrochloric acid solution. Benefiting from their unique structural merits including a three-dimensional (3D) open structure and high surface area, the resulting Ni-Fe NFs exhibit enhanced electrochemical properties.…”
mentioning
confidence: 99%